High frequency of a susceptible haplotype of the Mannose Binding Lectin gene, in the AnapiaSuana islands of Lake Titicaca - Sandoval S., José (2022)
We have analized the combination of variants at 4 sites of the gene MBL (mannose binding lectin) which is part of the immune system, in 19 normal individuals from the islands of Anapia-Suana in the Lake Titicaca. OnIy 3 combinations (haplotypes) were registered: LYPB, HYPA and LYPA; the proportion of the pressumed defective haplotype LYPB is 0.58 being the highest ever recorded. This haplotype is rare among European, Asian and African populations. It predisposes to infectious diseases as tuberculosis and AIDS as well as autoimmune diseases like reumatoid arthritis and lupus erithematosumo This finding lead our future efforts to elucidate the reason of this high frequency of LYPB and to determine its proportion in other islands of the Titicaca Lake.